Layered double hydroxide, method for producing layered double hydroxide, air electrode and metal-air secondary battery

The introduction of a layered double hydroxide composition with Ni, Fe, V, Co, and Mn, synthesized via a sol-gel process, addresses the suboptimal catalytic performance of existing LDHs in metal air secondary batteries, achieving improved catalytic functions for oxygen-related reactions.

JP7661490B2Active Publication Date: 2025-04-14NGK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023531396
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-02
Filing Date
2022-03-04
Publication Date
2025-04-14
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Existing layered double hydroxides (LDHs) used as catalysts for metal air secondary batteries do not achieve optimal catalytic functions, particularly for oxygen generation and reduction reactions.

Method used

A layered double hydroxide composition including Ni, Fe, V, Co, and Mn, with specific atomic ratios determined by energy dispersive X-ray spectroscopy, is developed. This composition is synthesized using a sol-gel process involving a solution of salts dissolved in an aqueous medium, with acetylacetone and propylene oxide added to promote gelation and stabilization.

Benefits of technology

The resulting LDH catalyst exhibits enhanced catalytic performance, including a lower onset potential and reduced resistance at given current densities, effectively promoting oxygen generation and reduction reactions in metal air secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661490000004
    Figure 0007661490000004
  • Figure 0007661490000005
    Figure 0007661490000005
  • Figure 0007661490000006
    Figure 0007661490000006
Patent Text Reader

Abstract

Provided is a layered double hydroxide having exceptional catalyst function. The layered double hydroxide according to an embodiment of the present invention includes the four elements Ni, Fe, V, and Co, and furthermore includes Mn as a fifth element. For example, the atomic ratio (Ni+Mn) / (Ni+Fe+V+CO+Mn) determined by energy-dispersive X-ray spectroscopy (EDS) is 0.6-0.8.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a layered double hydroxide, a method for producing a layered double hydroxide, an air electrode, and a metal-air secondary battery. [Background technology]

[0002] One of the candidates for innovative batteries is the metal-air secondary battery. Metal-air secondary batteries are secondary batteries that use a metal for the negative electrode and oxygen and / or water from the air as the active material for the positive electrode. At the positive electrode (air electrode) of a metal-air secondary battery, electrochemical reactions occur in which hydroxide ions are produced during discharge (oxygen reduction reaction, hereafter referred to as "ORR"), and oxygen is produced during charging (oxygen evolution reaction, hereafter referred to as "OER"). To promote this ORR / OER reaction, for example, a highly active catalyst is required.

[0003] As a catalyst for the air electrode, layered double hydroxides (LDHs) having a plurality of hydroxide layers and intermediate layers interposed between the hydroxide layers have been attracting attention and are used for various purposes as disclosed in Patent Document 1. In recent years, binary LDHs such as Ni-Fe-based LDHs and Ni-Co-based LDHs have been put to practical use as catalysts for air electrodes, but there is still much room for improvement in LDHs as catalysts. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 221497 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a layered double hydroxide having excellent catalytic function (for example, oxygen generation catalytic function). [Means for solving the problem]

[0006] The layered double hydroxide according to an embodiment of the present invention contains four elements, Ni, Fe, V and Co, and further contains Mn as a fifth element. In one embodiment, the layered double hydroxide has an atomic ratio of (Ni+Mn) / (Ni+Fe+V+Co+Mn) of 0.6 or more and 0.8 or less, as determined by energy dispersive X-ray spectroscopy (EDS). In one embodiment, the layered double hydroxide has an atomic ratio of Mn / Ni of 0.2 or more and 0.8 or less, as determined by energy dispersive X-ray spectroscopy (EDS). In one embodiment, the layered double hydroxide has an atomic ratio of Mn / (Ni+Fe+V+Co+Mn) greater than 0 and less than or equal to 0.4, as determined by energy dispersive X-ray spectroscopy (EDS). According to another aspect of the present invention, there is provided a method for producing the layered double hydroxide, comprising the steps of preparing a solution in which salts of Ni, Fe, V, Co and Mn are dissolved in an aqueous medium in a predetermined molar ratio, adding acetylacetone during or after the preparation of the solution, adding propylene oxide to the solution to which acetylacetone has been added, and leaving the solution to which propylene oxide has been added for a predetermined period of time. In one embodiment, the method includes leaving the solution to which propylene oxide has been added for a predetermined period of time to obtain a gel, and leaving the gel for a predetermined period of time to obtain a sol.

[0007] According to yet another aspect of the present invention, there is provided an air electrode comprising a porous current collector and a catalyst layer covering at least a portion of the porous current collector and containing the layered double hydroxide. According to yet another aspect of the present invention, there is provided a metal-air secondary battery comprising the above air electrode, a separator, an electrolyte, and a metal negative electrode. In one embodiment, the separator is a hydroxide ion conducting dense separator and the electrolyte is separated from the air electrode by the separator. Effect of the Invention

[0008] According to an embodiment of the present invention, the layered double hydroxide contains the four elements Ni, Fe, V and Co, and thus can achieve excellent catalytic function. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing a general configuration of a metal-air secondary battery according to one embodiment of the present invention. [Diagram 2] 2 is an enlarged view showing an example of a portion of the air electrode of the metal-air secondary battery shown in FIG. 1. [Diagram 3] 2 is a cross-sectional view conceptually showing an example of a separator (hydroxide ion conductive dense separator) of the metal-air secondary battery shown in FIG. [Figure 4A] 1 is an X-ray diffraction pattern of Example 1. [Figure 4B] 1 shows an SEM image and an element map image of Example 1. [Diagram 5] 1 is a graph showing the relationship between the potential and the current density relative to a hydrogen electrode, comparing Example 1, Comparative Example 1, and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0011] A. Layered double hydroxides The layered double hydroxide (LDH) according to the embodiment of the present invention contains four elements, Ni, Fe, V and Co. Specifically, it may be an LDH in which at least these four elements are composited. By containing at least the four elements, Ni, Fe, V and Co, it is possible to realize an excellent catalytic function (for example, an oxygen generating catalytic function). Specifically, in a catalytic activity evaluation when used as a catalyst for an air electrode of a metal-air secondary battery, it is possible to lower the on-set potential and / or to lower the potential at a predetermined current density (to lower the resistance). This can be presumed to be due to, for example, the number and / or density of active sites being increased by the large number of elements contained in the LDH, and the interaction between such active sites being increased. Note that the presumptions regarding the effects and mechanisms in this specification do not limit the present invention, and such presumptions do not restrict the present invention.

[0012] The LDH may contain at least one fifth element selected from the group consisting of Mn, Al, Zn, W, Cr and Ru in addition to the four elements. Specifically, the LDH may be an LDH in which at least the fifth element is complexed. By containing the fifth element, a more excellent catalytic function (for example, an oxygen generating catalytic function) can be realized.

[0013] The ratio of Ni to the sum of Ni, Fe, V, Co and the fifth element (hereinafter, these may be collectively referred to as "constituent elements") of the LDH, specifically, the atomic ratio of Ni / (Ni+Fe+V+Co) or the atomic ratio of Ni / (Ni+Fe+V+Co+fifth element) is preferably 0.3 or more and 0.8 or less, more preferably 0.35 or more and 0.75 or less, and even more preferably 0.4 or more and 0.7 or less. The atomic ratio of Fe / (Ni+Fe+V+Co) or the atomic ratio of Fe / (Ni+Fe+V+Co+fifth element) is preferably more than 0 and 0.3 or less, more preferably 0.005 or more and 0.25 or less, and even more preferably 0.01 or more and 0.2 or less. The atomic ratio of V / (Ni+Fe+V+Co) or the atomic ratio of V / (Ni+Fe+V+Co+fifth element) is preferably 0.04 or more and 0.49 or less, more preferably 0.06 or more and 0.35 or less, and even more preferably 0.07 or more and 0.3 or less. The atomic ratio of Co / (Ni+Fe+V+Co) or the atomic ratio of Co / (Ni+Fe+V+Co+fifth element) is preferably more than 0 and 0.2 or less, more preferably 0.005 or more and 0.18 or less, and even more preferably 0.01 or more and 0.17 or less. According to such a range, a more excellent catalytic function (for example, an oxygen generating catalytic function) can be realized.

[0014] In a preferred embodiment, the LDH contains at least Mn as the fifth element. Use of inexpensive Mn can contribute to cost reduction. In this embodiment, the atomic ratio of Mn / (Ni+Fe+V+Co+Mn) is preferably more than 0 and 0.4 or less, more preferably 0.05 or more and 0.35 or less, and further preferably 0.1 or more and 0.3 or less.

[0015] Since the valence of each element constituting the LDH is not necessarily certain, it is practically difficult to strictly specify the LDH by a general formula. In general, however, the LDH can be represented by the following general formula (I). (M 2+ ) 1-X (M 3+ ) X (OH)2(A n- )X / n mH2O (I) In formula (I), M 2+ is at least one divalent cation, M 3+ is at least one trivalent cation, and A n- is an n-valent anion, n is an integer equal to or greater than 1, and m is any real number (greater than 0). If the hydroxide layer of the LDH is mainly composed of Ni, Fe, V, Co and Mn, for example, in the above general formula (I), 2+ Ni 2+ and Mn 2+ M 3+ is Fe 3+ , V 3+ and Co 3+ The atomic ratio of (Ni+Mn) / (Ni+Fe+V+Co+Mn) is preferably 0.6 or more. On the other hand, the atomic ratio of (Ni+Mn) / (Ni+Fe+V+Co+Mn) is preferably 0.8 or less, more preferably 0.75 or less, and even more preferably 0.7 or less. The atomic ratio of Mn / Ni is preferably 0.2 or more and 0.8 or less, more preferably 0.25 or more and 0.75 or less, and even more preferably 0.3 or more and 0.7 or less.

[0016] In another embodiment, the LDH contains at least Al as the fifth element. In this embodiment, the atomic ratio of Al / (Ni+Fe+V+Co+Al) is preferably greater than 0 and equal to or less than 0.2, more preferably equal to or greater than 0.005 and equal to or less than 0.15, and even more preferably equal to or greater than 0.01 and equal to or less than 0.1.

[0017] In yet another embodiment, the LDH contains at least Zn as the fifth element. In this embodiment, the atomic ratio of Zn / (Ni+Fe+V+Co+Zn) is preferably greater than 0 and equal to or less than 0.3, more preferably equal to or greater than 0.005 and equal to or less than 0.25, and even more preferably equal to or greater than 0.01 and equal to or less than 0.2.

[0018] The above ratio (atomic ratio) can be determined by composition analysis using energy dispersive X-ray spectroscopy (EDS). For example, composition analysis can be performed using an energy dispersive X-ray analyzer (e.g., X-act, manufactured by Oxford Instruments), and the above ratio (atomic ratio) can be calculated from the analysis results.

[0019] The LDH may have a plurality of hydroxide layers and intermediate layers interposed between the hydroxide layers. Typically, the hydroxide layers contain constituent elements (typically in the form of ions) and OH groups, and the intermediate layers contain anions and HO. The anions are any suitable anions with a valence of one or more. Specific examples of the anions include NO3 - , CO3 2- , SO4 2- , O.H. - , Cl - Halide ions such as CO3 2- , O.H. - , Cl - The intermediate layer may contain one type of anion, or may contain two or more types of anions.

[0020] Typically, the LDH is particulate. In one embodiment, the LDH is a plate-like particle and may have any suitable shape in plan view. Specific examples of the shape in plan view include a circle, an ellipse, a rectangle, a triangle, a polygon, and an irregular shape. The size of the LDH (major axis of the primary particle) is, for example, 1 nm to 0.2 μm, and the thickness is, for example, 0.5 nm to 50 nm. Here, the "size of the LDH" refers to the size of the shape in plan view of the LDH, for example, the diameter in the case of a circle, the major axis in the case of an ellipse, and the length of the long side in the case of a rectangle. The size and thickness of the LDH can be measured, for example, by observation with a scanning electron microscope (SEM).

[0021] B. Preparation of Layered Double Hydroxides The LDH can be produced by any suitable method. In one embodiment, the LDH can be produced by a so-called sol-gel method. For example, the method for producing the LDH includes: preparing a solution in which salts of Ni, Fe, V, Co, and optionally the fifth element (in one embodiment, Mn) are dissolved in an aqueous medium at a predetermined molar ratio; adding acetylacetone (to the aqueous medium or the solution) during or after the preparation of the solution; adding propylene oxide to the solution to which acetylacetone has been added; and leaving the solution to which propylene oxide has been added for a predetermined period of time;

[0022] As the salt used in the preparation of the above solution, typically, any appropriate salt capable of forming the above intermediate layer is used. Examples of salts include nitrates, carbonates, sulfates, hydroxides, and halides (chlorides, iodides, bromides, and fluorides). For example, chlorides are used as the above salts. Chlorides are inexpensive and easily available, and have high solubility in aqueous media described below. The salts of the constituent elements may be the same type of salt (e.g., chlorides) or different types of salts. The valence (number of valences) of the constituent elements may be the same or different between the valence in the raw material (salt) and the valence in the obtained LDH. As a specific example of a case where the valences are different, CoCl2 is used as the starting material (salt) for Co, and Co in the obtained LDH is Co. 3+ It may take the form:

[0023] The amounts (feed ratios) of the salts of the constituent elements used are adjusted according to, for example, the desired composition of LDH.

[0024] The aqueous medium typically contains water. Examples of water that can be used include tap water, ion-exchanged water, pure water, and ultrapure water. Ultrapure water is preferred. Ultrapure water contains very little impurities, and therefore, for example, has very little effect on the reaction and can produce LDH with very few impurities. The aqueous medium may contain a hydrophilic organic solvent. Examples of the hydrophilic organic solvent include alcohols such as ethanol and methanol. The hydrophilic organic solvent can be used in an amount of preferably 100 to 200 parts by weight per 100 parts by weight of water.

[0025] It is preferable to stir the solution when preparing it. By stirring, it is possible to obtain an LDH that is uniform and has a composition very close to the designed value. The stirring time is, for example, 5 to 30 minutes.

[0026] Acetylacetone is added to the aqueous medium or the solution. Specifically, acetylacetone may be added during or after the preparation of the solution. By adding acetylacetone, spontaneous gelation and subsequent spontaneous disaggregation, which will be described later, can be realized, and as a result, fine particles of LDH can be obtained (aggregation and / or precipitation can be suppressed). In other words, it is possible to achieve both growth and stabilization of LDH particles, which are in a trade-off relationship.

[0027] The amount of acetylacetone added is preferably 0.008% to 0.036% (molar ratio), more preferably 0.016% to 0.018% (molar ratio), based on the total amount of the constituent elements. If the amount of acetylacetone added is within this range, for example, LDH with extremely few impurities can be obtained.

[0028] If necessary, the solution to which acetylacetone has been added is stirred for, for example, 15 to 60 minutes.

[0029] Propylene oxide is added to the solution to which acetylacetone has been added. Propylene oxide can function as a proton scavenger through protonation of epoxy oxygen and subsequent ring-opening by nucleophilic substitution reaction of the conjugate base. Such protonation and ring-opening can increase the pH of the solution, promoting crystallization (e.g., particulation) of LDH by coprecipitation. The amount of propylene oxide added is preferably 0.12% to 0.48% (molar ratio), more preferably 0.23% to 0.25% (molar ratio), based on the total amount of the constituent elements.

[0030] The solution containing propylene oxide is allowed to stand for a predetermined time (e.g., 12 to 36 hours). Specifically, the manufacturing method may include: allowing the solution containing propylene oxide to stand for a predetermined time to obtain a gel; and allowing the obtained gel to stand for a predetermined time to obtain a sol.

[0031] After the addition of propylene oxide, the solution may gel. Specifically, a gel containing a complex of the constituent elements may be formed. In practice, LDH is formed as a complex at this point, and it is presumed that this LDH aggregates to form a gel. The time left to stand until the gel is formed is, for example, 1 hour to 6 hours, and preferably 2 hours to 4 hours. If necessary, the solution may be stirred for a short time (for example, 30 seconds to 2 minutes) before being left to stand (i.e., immediately after the addition of propylene oxide).

[0032] The gel formed above is left for a predetermined time. The gel is deaggregated, and a sol containing LDH particles (e.g., plate-like fine particles) can be formed. The time for leaving until the sol is formed is, for example, 5 hours or more, and preferably 6 to 30 hours.

[0033] The sol may be subjected to a drying treatment. For example, the drying may be performed at room temperature (about 23° C.) from the viewpoint of suppressing aggregation of the obtained particles, or may be performed using a dryer. In the latter case, the drying temperature is preferably 60° C. to 90° C., and more preferably 70° C. to 80° C. The drying may be performed under reduced pressure (for example, vacuum drying). Each of the above steps may be performed at room temperature (about 23° C.).

[0034] A specific example of the sol-gel method can be carried out according to the method described in ACS Nano 2016, 10, 5550-5559, the disclosure of which is incorporated herein by reference.

[0035] In one embodiment, the production of LDH by the sol-gel method is carried out in the presence of a substrate (e.g., a porous sheet). For example, the production of LDH is carried out in a state where the substrate is immersed in the aqueous medium. In this embodiment, the LDH can be formed directly on the surface of the substrate. The porous sheet can correspond to the porous current collector of the air electrode described below. Therefore, this embodiment can also be a method for producing an air electrode. In this embodiment, the production of LDH and the binding and / or attachment of LDH to the porous current collector can be carried out simultaneously.

[0036] In another embodiment, the LDH may be produced by a coprecipitation method. For example, the method for producing the LDH includes dropping a raw material aqueous solution containing constituent elements into an aqueous solution containing carbonate ions under a condition of pH 9.5 to 12 to cause a reaction. For example, an aqueous NaOH solution is used to adjust the pH. The resulting reaction product is allowed to grow as necessary, for example, by stirring for a predetermined period of time. The resulting reaction product may be dried and / or crushed to obtain LDH particles.

[0037] The formation of the LDH can be confirmed, for example, by X-ray diffraction measurement. Typically, a first peak can be detected within a diffraction angle 2θ range of 10° to 12°, a second peak can be detected within a diffraction angle 2θ range of 22° to 24°, and a third peak can be detected within a diffraction angle 2θ range of 33° to 35°. The first peak can correspond to the (003) peak of LDH, the second peak can correspond to the (006) peak of LDH, and the third peak can correspond to the (012) peak of LDH.

[0038] The LDH contains the four elements of Ni, Fe, V and Co, and further contains the fifth element, and thus can achieve excellent catalytic function (e.g., oxygen generating catalytic function) regardless of the production method (e.g., whether it is a sol-gel method or a coprecipitation method).

[0039] C. Metal-air secondary battery 1 is a schematic diagram showing the general configuration of a metal-air secondary battery according to one embodiment of the present invention. The metal-air secondary battery 10 has an air electrode (positive electrode) 12, a metal negative electrode 14, a separator 16 disposed between the air electrode 12 and the metal negative electrode 14, and an electrolyte 18, all of which are contained in a container 20. The air electrode 12 is contained in the container 20 in a state in which it can come into contact with external air.

[0040] In the illustrated example, the separator 16 is provided adjacent to the air electrode 12, and the electrolyte 18 is separated from the air electrode 12 by the separator 16. The metal negative electrode 14 is immersed in the electrolyte 18. The metal negative electrode 14 may be made of any appropriate metal. Typically, the metal negative electrode 14 includes zinc or a zinc alloy. Specifically, the metal-air secondary battery 10 is a zinc-air secondary battery. Typically, a strong alkaline aqueous solution with a pH of about 14 (e.g., an aqueous potassium hydroxide solution) is used as the electrolyte 18.

[0041] C-1. Air electrode Fig. 2 is an enlarged view showing an example of a portion of the air electrode of the metal-air secondary battery shown in Fig. 1. The air electrode 12 includes a porous current collector 12a and a catalyst layer 12b that covers the surface of the porous current collector 12a. The catalyst layer 12b includes the above-mentioned LDH.

[0042] The porous current collector may have any suitable structure applicable to the air electrode of a metal-air secondary battery. The porous current collector may typically be made of a conductive material having gas diffusibility. Specific examples of such conductive materials include carbon, nickel, stainless steel, titanium, and combinations thereof. Carbon is preferred. Specific examples of the porous current collector include carbon paper, nickel foam, stainless steel nonwoven fabric, and combinations thereof. Carbon paper is preferred. The fiber diameter of the carbon fiber constituting the carbon paper is, for example, 10 μm to 20 μm. A commercially available porous material may be used as the porous current collector. The thickness of the porous current collector is preferably 0.1 mm to 1 mm, more preferably 0.1 mm to 0.5 mm, and even more preferably 0.1 mm to 0.3 mm. If the thickness is within such a range, for example, a reaction region, specifically a three-phase interface consisting of an ion-conducting phase (LDH), an electron-conducting phase (porous current collector), and a gas phase (air), can be widely secured. The porosity of the porous current collector (substantially the air electrode) is preferably 60% to 95%. When the porous current collector is carbon paper, the porosity is more preferably 60% to 90%. If the porosity is in this range, for example, excellent gas diffusibility can be ensured and a wide reaction region can be ensured. In addition, since the number of pores (voids) increases, clogging with generated water is less likely to occur. The porosity can be measured by mercury intrusion porosimetry.

[0043] The air electrode is prepared, for example, by depositing the LDH on a porous current collector. Specifically, the LDH may be produced in the presence of a porous current collector. In one embodiment, particulate LDH (e.g., plate-like fine particles) are bonded and / or attached (bonded, etc.) to the surface of a porous current collector 12a in the air electrode 12 to form a catalyst layer 12b.

[0044] The catalyst layer 12b may contain a second LDH having a different composition from the LDH. Specifically, the LDH constituting the catalyst layer 12b may have a single composition, or may be a mixture of two or more LDHs having different compositions. The LDH typically has the form of a plate-like particle, and the LDH may be bonded to the entire porous current collector (as a result, the entire porous current collector may be covered), or may be bonded to a part of the porous current collector (as a result, a part of the porous current collector may be covered). In one embodiment, the LDH (plate-like particle) is bonded such that its main surface is perpendicular or oblique to the surface of the porous current collector. In one embodiment, the LDH (plate-like particle) is connected to each other. With such a configuration, the reaction resistance can be reduced. In addition, the LDH can function not only as a catalyst (air electrode catalyst) but also as a hydroxide ion conductive material in the air electrode.

[0045] When the catalyst layer 12b is composed of a mixture of two or more LDHs with different compositions, the sizes of the LDHs (plate-like particles) of each composition are typically different from each other. With such a configuration, the supporting strength on the porous current collector 12a can be ensured. Furthermore, in one embodiment, the larger-sized LDH (plate-like particle) is bonded or the like so that its main surface is perpendicular or oblique to the surface of the porous current collector 12a. With such a configuration, the diffusion of oxygen into the porous current collector 12a can be promoted, and the amount supported on the porous current collector 12a can be increased.

[0046] The air electrode may further include an air electrode catalyst other than the LDH and / or a hydroxide ion conductive material. Specific examples of the air electrode catalyst other than the LDH and / or the hydroxide ion conductive material include metal oxides, metal nanoparticles, carbon materials, and combinations thereof. The air electrode may further include a material capable of adjusting the moisture content. In one embodiment, the LDH may function as such a material. Other specific examples of the material capable of adjusting the moisture content include zeolite, calcium hydroxide, and combinations thereof.

[0047] The air electrode 12 may be composed of a single layer including a porous current collector 12a and a catalyst layer 12b covering the surface of the porous current collector 12a, as shown in FIG. 2, or may have an outer layer including a porous current collector 12a and a catalyst layer 12b covering the surface of the porous current collector 12a, as well as an inner layer having a configuration different from the outer layer, formed on the side (inner side) where the separator 16 is arranged, as shown in FIG. 2.

[0048] The inner layer is formed, for example, by filling a specific inner portion (end in the thickness direction) of the porous current collector with a mixture containing a hydroxide ion conductive material, a conductive material, an air electrode catalyst, and an organic polymer.

[0049] As the hydroxide ion conductive material, any appropriate material having hydroxide ion conductivity can be used. Preferably, it is LDH. The LDH is not limited to the LDH according to the embodiment of the present invention described in the above section A, and any appropriate LDH can be used. The LDH can be typically represented by the following general formula (II). (M 2+ ) 1-Y (M 3+ ) Y (OH)2(A n- ) Y / n mH2O (II) In formula (II), M 2+ is at least one divalent cation, M 3+ is at least one trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, m is an arbitrary real number (exceeding 0), and Y is 0.1 to 0.4. 2+ For example, Ni 2+ , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ Examples include: 3+ For example, Fe 3+ , Al 3+ , Co 3+ , Cr 3+ , In3+ , V 3+ Specific examples of LDH include Mg-Al-based LDH and LDH containing a transition metal (e.g., Ni-Fe-based LDH, Co-Fe-based LDH, Ni-Fe-V-based LDH). The hydroxide ion conductive material may be the same material as the air electrode catalyst.

[0050] Examples of the conductive material include conductive ceramics, carbon materials, and combinations thereof. Specific examples of conductive ceramics include LaNiO3, LaSr3Fe3O 10 Specific examples of carbon materials include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and combinations thereof. The conductive material may also be the same material as the air electrode catalyst.

[0051] The air electrode catalyst may be LDH, other metal hydroxides, metal oxides, metal nanoparticles, carbon materials, nitrides, or combinations thereof. Preferably, LDH, metal oxides, metal nanoparticles, carbon materials, or combinations thereof. The LDH is as described above for the hydroxide ion conductive material. Specific examples of metal hydroxides include Ni-Fe-OH, Ni-Co-OH, and combinations thereof. These may further contain a third metal element. Specific examples of metal oxides include Co3O4, LaNiO3, LaSr3Fe3O 10 , and combinations thereof. Metal nanoparticles are typically metal particles with a particle size of 2 nm to 30 nm. Specific examples of metal nanoparticles include Pt and Ni-Fe alloys. Specific examples of carbon materials, as described above, include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and combinations thereof. The carbon material may further contain metal elements and / or other elements such as nitrogen, boron, phosphorus, and sulfur. With such a configuration, the catalytic performance of the carbon material can be improved. An example of the nitride is TiN.

[0052] As the organic polymer, any appropriate binder resin can be used. Specific examples of the organic polymer include butyral resins, vinyl alcohol resins, celluloses, vinyl acetal resins, etc., and preferably butyral resins.

[0053] The air electrode 12 may be provided in advance as a laminate with the separator 16 .

[0054] C-2. Separator As the separator, for example, a hydroxide ion conductive dense separator is used. With the hydroxide ion conductive dense separator, the electrolyte is isolated from the air electrode, and the evaporation of the water contained in the electrolyte can be suppressed. As the hydroxide ion conductive dense separator, a LDH separator can be typically used. The LDH separator is typically used in a metal-air secondary battery, and such a metal-air secondary battery has an excellent advantage in that it can prevent both a short circuit between the positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide. In addition, the denseness of the LDH separator has an advantage in that it can effectively suppress the evaporation of the water contained in the electrolyte. On the other hand, since the LDH separator prevents the electrolyte from penetrating into the air electrode, the electrolyte is not present in the air electrode, and as a result, compared to a metal-air secondary battery using a general separator (for example, a porous polymer separator) that allows the electrolyte to penetrate into the air electrode, the hydroxide ion conductivity tends to be lower and the charge / discharge performance tends to be lower. By using a laminate of an air electrode and an LDH separator according to an embodiment of the present invention, it is possible to eliminate such inconveniences while maintaining the excellent advantages of the LDH separator. Note that, in the following description, the contents of the LDH separator are also applicable to hydroxide ion conductive dense separators other than the LDH separator, so long as technical consistency is not impaired. In other words, in the following description, the LDH separator can be read as the hydroxide ion conductive dense separator, so long as technical consistency is not impaired.

[0055] Any suitable configuration can be adopted as the LDH separator. For example, the configurations described in International Publication No. 2013 / 073292, International Publication No. 2016 / 076047, International Publication No. 2016 / 067884, International Publication No. 2015 / 146671, and International Publication No. 2018 / 163353 can be adopted as the LDH separator. The descriptions in these publications are incorporated herein by reference.

[0056] In one embodiment, the LDH separator may include a porous substrate and a layered double hydroxide (LDH) and / or an LDH-like compound. In this specification, the term "LDH separator" is defined as a separator containing LDH and / or an LDH-like compound (LDH and LDH-like compounds may be collectively referred to as hydroxide ion-conducting layered compounds), and selectively passing hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion-conducting layered compounds. In this specification, the term "LDH-like compound" refers to a hydroxide and / or oxide having a layered crystal structure similar to LDH, which may not be strictly called LDH, and can be considered to be an equivalent of LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds.

[0057] The LDH-like compound preferably contains Mg and Ti, and if necessary, Y and / or Al. In this way, by using an LDH-like compound that is a hydroxide and / or oxide having a layered crystal structure containing at least Mg and Ti as a hydroxide ion conductive material instead of a conventional LDH, a hydroxide ion conductive separator that is excellent in alkali resistance and can more effectively suppress short circuits caused by zinc dendrites can be provided. Therefore, a preferred LDH-like compound is a hydroxide and / or oxide having a layered crystal structure containing Mg and Ti, and if necessary, Y and / or Al, and a more preferred LDH-like compound is a hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y and Al. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired. In one embodiment, it is preferable that the LDH-like compound does not contain Ni.

[0058] The LDH-like compound can be identified by X-ray diffraction. Specifically, when the surface of the LDH separator is measured by X-ray diffraction, a peak derived from the LDH-like compound is typically detected in the range of 5°≦2θ≦10°, more typically in the range of 7°≦2θ≦10°. As described above, LDH is a substance having an alternating laminate structure in which exchangeable anions and H2O exist as intermediate layers between stacked hydroxide layers. In this regard, when LDH is measured by X-ray diffraction, a peak due to the crystal structure of LDH (i.e., the (003) peak of LDH) is essentially detected at a position of 2θ=11° to 12°. In contrast, when an LDH-like compound is measured by X-ray diffraction, a peak is typically detected in the above-mentioned range shifted to the lower angle side from the above-mentioned peak position of LDH. In addition, the interlayer distance of the layered crystal structure can be determined by the Bragg formula using 2θ corresponding to the peak derived from the LDH-like compound in the X-ray diffraction pattern. The interlayer distance of the layered crystal structure constituting the LDH-like compound thus determined is typically 0.883 nm to 1.8 nm, and more typically 0.883 nm to 1.3 nm.

[0059] The atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound determined by energy dispersive X-ray spectroscopy (EDS) is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. The atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. The atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. The atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within the above range, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Incidentally, LDH, which has been conventionally known as an LDH separator, can be represented by the above formula (II). In contrast, the above atomic ratio in an LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that an LDH-like compound generally has a composition ratio (atomic ratio) different from that of a conventional LDH. It is preferable that the composition analysis by EDS is performed by using an energy dispersive X-ray analyzer (e.g., X-act, manufactured by Oxford Instruments) by, for example, 1) taking an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in a point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.

[0060] As conceptually shown in FIG. 3, the separator (LDH separator) 16 preferably includes a porous substrate (polymeric porous substrate) 16a made of a polymer material and an LDH 16b that blocks the pores of the porous substrate. In practice, the pores of the porous substrate 16a do not need to be completely blocked, and a small amount of residual pores P may exist. By including a polymeric porous substrate, the separator can bend even when pressurized and is not easily broken, so that the separator can be housed in a battery container and pressurized in a direction in which each battery element is in close contact with each other together with other battery elements (negative electrodes, etc.). Such pressurization is particularly advantageous when a stacked battery is constructed by alternately incorporating a plurality of air electrodes / separator laminates together with a plurality of metal negative electrodes in a battery container. Similarly, it is also advantageous when a battery module is constructed by housing a plurality of stacked batteries in one module container. For example, by pressurizing a metal-air secondary battery, the gap that allows the growth of metal dendrites between the negative electrode and the LDH separator can be minimized (preferably eliminated), and thus more effective prevention of metal dendrite growth can be expected. Furthermore, by filling the pores of the polymeric porous substrate with LDH to make it highly dense, it is possible to provide an LDH separator that can more effectively suppress short circuits caused by metal dendrites. In Fig. 3, the LDH 16b region is depicted as not being connected between the upper and lower surfaces of the LDH separator 16, but this is because it is depicted two-dimensionally as a cross section, and in an actual LDH separator, the LDH 16b region is connected between the upper and lower surfaces, thereby ensuring the hydroxide ion conductivity of the LDH separator 16.

[0061] The polymeric porous substrate has the following advantages: 1) flexibility (so it is not easily broken even when it is thinned); 2) easy to increase the porosity; 3) easy to increase the conductivity (because the thickness can be reduced while increasing the porosity); and 4) easy to manufacture and handle. In addition, by taking advantage of the advantage derived from the flexibility of 1), 5) the LDH separator including the polymeric porous substrate can be easily folded or sealed and joined. Specific examples of polymeric materials include polystyrene, polyethersulfone, polyolefin (e.g., polyethylene, polypropylene), epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), cellulose, nylon, and combinations thereof. In terms of thermoplastic resins suitable for hot pressing, polystyrene, polyethersulfone, polyolefin (e.g., polyethylene, polypropylene), epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), nylon, and combinations thereof are preferably used. All of these materials have alkali resistance as resistance to the electrolyte. More preferred polymer materials are polyolefins such as polypropylene and polyethylene, which are excellent in hot water resistance, acid resistance, and alkali resistance, and are low cost, and polypropylene or polyethylene is particularly preferred. When the porous substrate is made of a polymer material, it is particularly preferred that the LDH is incorporated throughout the entire thickness of the porous substrate (for example, most or almost all of the pores inside the porous substrate are filled with LDH). As such a polymeric porous substrate, a commercially available polymeric microporous membrane can be used. As described above, the LDH separator 16 can achieve the above-mentioned excellent pressure resistance and processability / assembly while maintaining the excellent properties attributable to the LDH by offsetting or reducing the hardness and brittleness of the LDH, which is a ceramic material, with the flexibility and toughness of the polymeric porous substrate.

[0062] As the LDH16b, any appropriate LDH can be used as long as it can close the pores of the polymeric porous substrate and densify the LDH separator. Specifically, the LDH may be an LDH according to the embodiment of the present invention, or any LDH other than the embodiment of the present invention. The LDH according to the embodiment of the present invention is as described in the above section A. As for the other LDH, for example, the LDH described in the above section C-1 may be used, or the LDH described in the above International Publication incorporated by reference in this specification may be used.

[0063] The LDH separator 16 preferably has fewer residual pores P (pores not blocked by LDH). The average porosity of the LDH separator due to the residual pores P is, for example, 0.03% or more and less than 1.0%, preferably 0.05% to 0.95%, more preferably 0.05% to 0.9%, further preferably 0.05% to 0.8%, and particularly preferably 0.05% to 0.5%. If the average porosity is within such a range, the pores of the porous substrate 16a are sufficiently blocked by the LDH 16b, and an extremely high degree of denseness can be achieved, and as a result, short circuits due to metal dendrites can be more effectively suppressed. In addition, a significantly high ion conductivity can be achieved, and the LDH separator 16 can fully function as a hydroxide ion conductive dense separator. The average porosity can be obtained by: a) polishing the cross section of the LDH separator with a cross-section polisher (CP), b) obtaining two cross-sectional images of the functional layer at 50,000x magnification using a FE-SEM (field emission scanning electron microscope), and c) calculating the porosity of each of the two fields of view using image inspection software (e.g., HDevelop, manufactured by MVTec Software) based on the image data of the obtained cross-sectional images, and then calculating the average value of the obtained porosities.

[0064] The LDH separator 16 is typically gas-impermeable and / or water-impermeable. In other words, the LDH separator 16 is so dense that it is gas-impermeable and / or water-impermeable. In this specification, "gas-impermeable" means that even if helium gas is brought into contact with one side of the object to be measured in water at a differential pressure of 0.5 atm, no bubbles due to helium gas are generated from the other side. In addition, in this specification, "water-impermeable" means that water that has come into contact with one side of the object to be measured does not permeate to the other side. As a result, the LDH separator 16 selectively passes only hydroxide ions due to its hydroxide ion conductivity, and can function as a battery separator. Furthermore, it is extremely effective in preventing short-circuiting between positive and negative electrodes by physically preventing penetration of the separator by metal dendrites generated during charging. Since the LDH separator has hydroxide ion conductivity, it enables the efficient movement of hydroxide ions required between the positive electrode and the negative electrode, thereby realizing the charge / discharge reaction at the positive electrode and the negative electrode.

[0065] The LDH separator 16 has a He permeability per unit area of ​​preferably 3.0 cm / min·atm or less, more preferably 2.0 cm / min·atm or less, and even more preferably 1.0 cm / min·atm or less. If the He permeability is in this range, the permeation of metal ions in the electrolyte can be suppressed extremely effectively. As a result, it is considered in principle that the growth of metal dendrites can be effectively suppressed when used in a metal-air secondary battery. The He permeability is measured through a process of supplying He gas to one side of the separator to allow the He gas to permeate the separator, and a process of calculating the He permeability to evaluate the denseness of the hydroxide ion conductive dense separator. The He permeability is calculated by the formula F / (P×S) using the amount of He gas permeated per unit time F, the differential pressure P applied to the separator during He gas permeation, and the membrane area S through which the He gas permeates. By evaluating the gas permeability using He gas in this way, it is possible to evaluate the presence or absence of denseness at an extremely high level, and as a result, it is possible to effectively evaluate a high level of denseness, such as not allowing substances other than hydroxide ions (especially metal ions that cause metal dendrite growth) to permeate as much as possible (permeating only a very small amount). This is because He gas has the smallest structural unit among atoms or molecules that can constitute gas, and has extremely low reactivity. That is, He does not form molecules, and He gas is composed of He atoms alone. On the other hand, hydrogen gas is composed of H2 molecules, so that He atoms alone are smaller as a gas structural unit. In the first place, H2 gas is dangerous because it is a flammable gas. In this way, by adopting the index of He gas permeability defined by the above formula, it is possible to easily and objectively evaluate the denseness regardless of various sample sizes and differences in measurement conditions. In this way, it is possible to easily, safely, and effectively evaluate whether a separator has a sufficiently high denseness suitable for a separator for a metal-air secondary battery.

[0066] The separator 16 has a thickness of, for example, 5 μm to 200 μm.

[0067] By using the air electrode in combination with the hydroxide ion conductive dense separator, the resulting metal-air secondary battery can simultaneously satisfy the following advantages: (i) it can prevent both short circuits between the positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide, (ii) it can suppress the evaporation of water contained in the electrolyte, and (iii) it has excellent charge and discharge performance. EXAMPLES

[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0069] <Example 1> An aqueous medium containing 45% by weight of ultrapure water and 55% by weight of ethanol was prepared. 8.34 mmol of NiCl2, 2.98 mmol of FeCl3, 2.98 mmol of VCl3, 0.31 mmol of CoCl2, and 4.21 mmol of Mn(NO3)2 were dissolved in this aqueous medium, and stirred for 10 minutes to prepare a solution. Acetylacetone was added to this solution. The amount of acetylacetone added was 0.017% (molar ratio) with respect to the total amount of Ni, Fe, V, Co, and Mn elements. This solution was stirred for 30 minutes, and then propylene oxide was added. The amount of propylene oxide added was 0.24% (molar ratio) with respect to the total amount of Ni, Fe, V, Co, and Mn elements. This solution was stirred for 1 minute, and then left to stand for 3 hours. As a result, the solution spontaneously gelled. The obtained gel was left to stand for another 24 hours, and spontaneously turned into a sol. The series of operations was performed at room temperature.

[0070] The resulting sol was separated by centrifugation, and the resulting particles were washed with water and then with ethanol in that order (to remove chlorides, nitrates, reaction by-products, etc.).The particles were then dried at room temperature and crushed in a mortar to obtain a sample powder.

[0071] <Examples 2 to 10, Experimental Example 1, and Comparative Examples 1 to 3> A sample powder was obtained in the same manner as in Example 1, except that the composition ratio shown in Table 1 was used.

[0072] <Experimental Examples 2-1 to 2-4> A sample powder was obtained in the same manner as in Example 1, except that the composition ratio shown in Table 2 was used.

[0073] <Experimental Examples 3-1 to 3-2> A sample powder was obtained in the same manner as in Example 1, except that the composition ratio shown in Table 3 was used.

[0074] The obtained sample was subjected to the following measurements. The X-ray diffraction pattern of Example 1 is shown in Fig. 4A, and the SEM image and element map image of Example 1 are shown in Fig. 4B. 1. X-ray diffraction measurement The X-ray diffraction pattern of the obtained sample was obtained using RINT-TTRIII manufactured by Rigaku Corp. The measurement conditions were as follows: ·X-ray source: Cu-Kα ray Output: 50kV, 300mA Step angle: 0.020° Scan speed: 2.00° / min Diffraction angle 2θ: 5°~70° 2.SEM-EDX measurement The obtained samples were subjected to elemental mapping by energy dispersive X-ray spectroscopy (SEM-EDX) using a scanning electron microscope (SEM). Specifically, a scanning transmission electron microscope (SU3500, Hitachi High-Technologies Corporation) and an attached energy dispersive X-ray analyzer (HORIBA, Ltd., detector: X-MAX20, analyzer: EX-370) were used to 1) capture images at an accelerating voltage of 10 kV and a magnification of 20,000 times, 2) perform three-point analysis with an interval of about 5 μm in point analysis mode, 3) repeat the above 1) and 2) once more, and 4) calculate the average value of a total of six points, thereby performing composition analysis.

[0075] 4A, peaks derived from LDH (the first, second and third peaks) are observed in the X-ray diffraction pattern of Example 1, and therefore it can be said that LDH was obtained in Example 1. Note that similar peaks derived from LDH were observed in the X-ray diffraction patterns of other Examples, Comparative Examples and Experimental Examples. As shown in FIG. 4B, in the element map image of Example 1, the mapping shapes of Ni, Fe, V, Co and Mn are substantially the same, and these elements are present at almost the same positions, so it can be said that these elements are not simply mixed but are composited. In addition, it was confirmed that the results of the composition analysis correspond to the charging ratio of the raw materials (salt). Note that the same results as in Example 1 were obtained in the element map images of other Examples, Comparative Examples and Experimental Examples.

[0076] [Evaluation of catalytic activity] The catalytic performance of the obtained samples for OER was evaluated using the rotating ring disk electrode (RRDE) measurement method. Specifically, a "rotating ring-disk electrode device" manufactured by BAS was used as the measuring device. A platinum ring-glassy carbon (GC) disk electrode manufactured by BAS was used as the electrode. A 0.1 M KOH aqueous solution was used as the electrolyte. 5 mg of the obtained sample and 3000 μL of butanol were mixed by ultrasonic waves for 1 hour to obtain a measurement solution. After casting 6 μL of this measurement solution onto the disk electrode and drying, 4 μL of a 0.1 wt % Nafion (registered trademark, manufactured by Sigma-Aldrich) solution was cast onto the disk electrode, and convection voltammetry was performed at a rotation speed of 1600 rpm, a chiller temperature of 25°C, and in an oxygen atmosphere. From the relationship between the potential and current density relative to the hydrogen electrode, the start-up potential and current density of 10 mA / cm were obtained. 2 The potential at which the potential rises was determined was the potential at which ΔA / ΔV became 3. The evaluation results are shown in Tables 1 to 3. Moreover, a graph comparing the relationship between the potential and the current density with respect to the hydrogen electrode for Example 1, Comparative Example 1, and Comparative Example 3 is shown in FIG.

[0077] [Table 1]

[0078] [Table 2]

[0079] [Table 3]

[0080] As is clear from Table 1 and FIG. 5, the Example (quinary system) had a higher onset potential and / or current density of 10 mA / cm than Comparative Example 1 (ternary system) and Comparative Example 3 (binary system). 2 The potential at is small.

[0081] [Charge / discharge test] For Example 1 and Comparative Example 3, a charge / discharge test was carried out according to the following procedure.

[0082] (Creating the air electrode) <Example 1> An aqueous medium containing 45% by weight of ultrapure water and 55% by weight of ethanol was prepared. 8.34 mmol of NiCl2, 2.98 mmol of FeCl3, 2.98 mmol of VCl3, 0.31 mmol of CoCl2, and 4.21 mmol of Mn(NO3)2 were dissolved in this aqueous medium, and stirred for 10 minutes to prepare a solution. Acetylacetone was added to this solution. The amount of acetylacetone added was 0.017% (molar ratio) based on the total amount of Ni, Fe, V, Co, and Mn elements. This solution was stirred for 30 minutes, and then propylene oxide was added. The amount of propylene oxide added was 0.24% (molar ratio) based on the total amount of Ni, Fe, V, Co, and Mn elements. This solution was stirred for 1 minute, and the resulting solution was impregnated into a 3 cm x 3 cm piece of carbon paper (manufactured by SGL, product name "Sigracet (registered trademark)") and then left to stand for 3 hours. As a result, the solution spontaneously gelled. The resulting gel was left to stand for a further 24 hours, whereupon it spontaneously turned into a sol. The series of operations was carried out at room temperature. The surface of the treated carbon paper was washed with ion-exchanged water and then dried in a dryer at 80°C for 3 hours. In this way, an air electrode was obtained.

[0083] <Comparative Example 3> An air electrode was obtained in the same manner as in Example 1, except that the composition ratio shown in Table 1 was used.

[0084] (Preparation of evaluation cells) An evaluation cell was prepared as shown in Fig. 1. Specifically, a metal zinc plate (negative electrode) was placed in a container, a nonwoven fabric (not shown in Fig. 1) was placed on top of the metal zinc plate, and a 5.4 M KOH aqueous solution (electrolyte) was added to the obtained evaluation cell so that it was higher than the bottom surface of the separator but did not reach the top surface of the separator. Next, the separator and the air electrode obtained above were placed in this order on the nonwoven fabric to obtain an evaluation cell.

[0085] (evaluation) A charge / discharge test was performed on the obtained evaluation cell (air electrode side) under water vapor saturation (25°C) and oxygen gas flow (200cc / min). An electrochemical measurement device (Hokuto Denko Corporation, "HZ-Pro S12") was used for the charge / discharge test. The charge / discharge current density was 8mA / cm. 2 The battery was discharged for 10 minutes at 1000 V and then charged for 10 minutes (1 cycle). This procedure was repeated for a total of 3 cycles. The overvoltage at a capacity of 0.5 mAh in the second cycle was 0.616 V in Example 1 and 0.762 V in Comparative Example 3. It is considered that the charge / discharge reaction was further promoted in Example 1, which resulted in a decrease in the overvoltage. [Industrial Applicability]

[0086] The layered double hydroxide according to an embodiment of the present invention can be suitably used as a catalyst for the air electrode of a metal-air secondary battery. [Explanation of symbols]

[0087] 10 Metal-air secondary battery 12 Air electrode (positive electrode) 12a Porous current collector 12b Catalyst layer (layered double hydroxide) 14 Metallic anode 16 Separator 18 Electrolyte

Claims

1. Contains four elements: Ni, Fe, V and Co; Further containing Mn as a fifth element, the atomic ratio of Ni / (Ni+Fe+V+Co+Mn) is 0.3 or more and 0.8 or less, as determined by energy dispersive X-ray spectroscopy (EDS); the atomic ratio of Fe / (Ni+Fe+V+Co+Mn) is greater than 0 and less than or equal to 0.3, as determined by energy dispersive X-ray spectroscopy (EDS); the atomic ratio of V / (Ni+Fe+V+Co+Mn) is 0.04 or more and 0.49 or less, as determined by energy dispersive X-ray spectroscopy (EDS); the atomic ratio of Co / (Ni+Fe+V+Co+Mn) is greater than 0 and less than or equal to 0.2, as determined by energy dispersive X-ray spectroscopy (EDS); the atomic ratio of Mn / (Ni+Fe+V+Co+Mn) is greater than 0 and less than or equal to 0.4, as determined by energy dispersive X-ray spectroscopy (EDS); Layered double hydroxides.

2. 2. The layered double hydroxide according to claim 1, wherein the atomic ratio of (Ni+Mn) / (Ni+Fe+V+Co+Mn) is 0.6 or more and 0.8 or less, as determined by energy dispersive X-ray spectroscopy (EDS).

3. 3. The layered double hydroxide according to claim 1, wherein the atomic ratio of Mn / Ni, as determined by energy dispersive X-ray spectroscopy (EDS), is 0.2 or more and 0.8 or less.

4. A method for producing the layered double hydroxide according to any one of claims 1 to 3, comprising the steps of: Preparing a solution in which salts of Ni, Fe, V, Co and Mn are dissolved in an aqueous medium in a predetermined molar ratio; adding acetylacetone during or after preparation of said solution; adding propylene oxide to the solution to which acetylacetone has been added; and leaving the solution containing the propylene oxide for a predetermined period of time; A manufacturing method comprising:

5. 5. The method of claim 4, further comprising: allowing the solution to which the propylene oxide has been added to stand for a predetermined period of time to obtain a gel; and allowing the gel to stand for a predetermined period of time to obtain a sol.

6. A porous current collector; A catalyst layer covering at least a portion of the porous current collector and comprising the layered double hydroxide according to any one of claims 1 to 3; The air electrode has

7. A metal-air secondary battery comprising the air electrode according to claim 6, a separator, an electrolyte, and a metal negative electrode.

8. 8. The metal-air secondary battery of claim 7, wherein the separator is a hydroxide ion conductive dense separator, and the electrolyte is isolated from the air electrode by the separator.

Citation Information

Patent Citations

  • Carbonate precursor and preparation method and application thereof

    CN108862406A

  • Method for preparing 2,5-furan dicarboxylic acid through electro-catalytic oxidation of 5-hydroxymethylfurfural by hydrotalcite-based layered catalyst

    CN111472020A

  • Functional layer including layered double hydroxide, and composite material

    WO2017221497A1

  • Layered double hydroxide, catalyst for water electrolysis cells, water electrolysis cell, water electrolysis device, and layered double hydroxide production method

    WO2020250590A1

  • Layered double hydroxide and method for production thereof, and air electrode and metal-air secondary battery that use said layered double hydroxide

    WO2021176869A1